2023
DOI: 10.1021/acsomega.3c01988
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Dermatophytosis across the World’s Populations: Potential Benefits from Nanocarrier-Based Therapies and Rising Challenges

Puja Keshwania,
Narinder Kaur,
Jyoti Chauhan
et al.

Abstract: The most prevalent infection in the world is dermatophytosis, which is a major issue with high recurrence and can affect the entire body including the skin, hair, and nails. The major goal of this Review is to acquire knowledge about cutting-edge approaches for treating dermatophytosis efficiently by adding antifungals to formulations based on nanocarriers in order to overcome the shortcomings of standard treatment methods. Updates on nanosystems and research developments on animal and clinical investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 216 publications
0
2
0
Order By: Relevance
“…In contrast, other dermatophytes, like Trichophyton verrucosum, Trichophyton violaceum, and Microsporum ferrugineum, remain more prevalent in specific regions of Europe, Asia, and Africa. Furthermore, Trichophyton tonsurans, is more commonly found in the United Kingdom and North/South America [23]. On the other hand, studies have shown that Trichophyton indotineae, which originated in the Indian subcontinent, has spread to numerous countries worldwide [24].…”
Section: Fungal Factorsmentioning
confidence: 99%
“…In contrast, other dermatophytes, like Trichophyton verrucosum, Trichophyton violaceum, and Microsporum ferrugineum, remain more prevalent in specific regions of Europe, Asia, and Africa. Furthermore, Trichophyton tonsurans, is more commonly found in the United Kingdom and North/South America [23]. On the other hand, studies have shown that Trichophyton indotineae, which originated in the Indian subcontinent, has spread to numerous countries worldwide [24].…”
Section: Fungal Factorsmentioning
confidence: 99%
“…Dermatophytosis fungal illnesses, often known as tinea infections, are the most prevalent type of infection with high recurrence and can affect the entire body. They can be classified into three distinct genera, specifically Trichophyton, Microsporum, and Epidermophyton [22]. They can be spread from human to human (anthropophilic), animal to human (zoophilic), or soil to human (geophilic) [23].…”
Section: Superficial/cutaneous Mycosesmentioning
confidence: 99%